Applications of Ultrasound in the Postoperative Period: A Review - Long, Emily; Maselli, Amy; Barron, Sivana; Morgenstern, Monica; Comer, Carly D.; Chow, Kaimana; Cauley, Ryan; Lee, Bernard T. (Journal of Reconstructive Microsurgery, 2022)
Background Recent advances in ultrasound technology have further increased its potential for routine use by plastic and reconstructive surgeons.Methods An extensive literature review was performed to determine the most common applications of ultrasound in the postoperative care of plastic and reconstructive surgery patients.Results In contrast with other available imaging modalities, ultrasound is cost-effective, rapid to obtain, eliminates the need for ionizing radiation or intravenous contrast, and has virtually no contraindications. In addition to its diagnostic capabilities, ultrasound can also be used to facilitate treatment of common postoperative concerns conveniently at the bedside or in an office setting.Conclusion This article presents a review of the current applications of ultrasound imaging in the postoperative care of plastic and reconstructive surgery patients, including free flap monitoring following microsurgery, diagnosis and treatment of hematoma and seroma, including those associated with BIA-ALCL, and breast implant surveillance.
Keywords: ultrasound; postoperative; plastic surgery; microsurgery; seroma; breast surgery